Discussions on education policies in media: Media representations of education activists in Turkey - Sen, A. Fulya (Sage Publications Ltd, 2019)
This study examines the media representations of Turkey's educational labour union, Egitim-Sen. In so doing, it analyses the news coverage of the protests of Egitim-Sen against the education policies of the Justice and Development Party (AKP) government, structured by an Islamist political perspective. In this study, the content analysis has been carried out in order to investigate the attitude of the news media towards the education activism, as well as in order to take in issues of meaning and context. This analysis involves the online newspaper debates pertaining to the 13 February 2015 strike action of Egitim-Sen, and the new curriculum announced in July 2017. This study aims to reveal how the struggles of Egitim-Sen against the Islamification of the education system in Turkey are represented in the media, how Turkish media attempts to generate powerful voices, as well as how the media ignores the voices of dissidents. It has been concluded that Egitim-Sen is underrepresented in the mainstream news media.
Keywords: Education policies; media representations; public sphere; education activism; Egitim-Sen